Apresentações de livros didáticos : um estudo discursivo sobre a posição ideológica do sujeito - Santana, Moniza de Oliveira (2016)
This work proposes a discursive analysis of the ideological position of the subject in textbooks presentations of the Portuguese Language. For this study, we bring out the theories of the Discourse Analysis of French influence, from the postulates of Michel Pêcheux (1997a, 1997b) and contributions of Eni Orlandi (2001, 2002, 2007); We also study the prospects of Barbara Freitag (1997), Marisa Grigoletto (1999) and Deusa Souza (1999) on the Textbook. In this context, the textbook presentations as object of analysis are considered material (text) historical-linguistic. According to this perspective, taken by elementary externals, which allowed us to work with basic notions: subject, discourse, ideology, discursive formation and interdiscourse. So, we analyzed how the subject is constructed from a particular position and from what it has been said, the discursive memory. We observed the discursive operation in the dispersion of meanings that construct the ideological position of the subject. In order to do this, We selected a corpus with ten presentations of textbooks of Elementary school and of High school from the following publishers: FTD, Saraiva, Scipione, Moderna, Atual e Ática. Finally, we found, in our analysis, that the subject is approached ideologically by discursive formations of the market, in which the textbook is meant as a merchandise; we also observed the discursive formation of the new, a speech from the perspective of innovation of NCPs (1997), and it proposes a language-oriented education and knowledge while interacting. We also noticed the discursive formation mobilizing, which (re)means the textbook as a helper and not dominant in the teaching/learning process of Portuguese language; We also highlighted the discursive formation of success, which is the student as an individual who has "success" by getting approval in the best national examinations (vestibulares, ENEM).